Analisis Kebutuhan LKPD Praktikum Berbasis Inkuiri Terbimbing Berbantu Teka-teki Silang pada Materi Vertebrata untuk Peserta Didik SMA - Alfionita Anggraini; Ristiono Ristiono; Ardi Ardi; Relsas Yogica (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The study aims to identify the needs of students for the LKPD practicum as a guide book in pratical activities. As well as addressing problems in the selection of learning media in accordance with the learning activities carried out. The method used in this research is descriptive method with quantitative and qualitative approaches. Data collection techniques through interviews and distributing questionnaires to a biology teacher who teaches in class X and 28 students in class X IPA 3 SMAN 1 VII Koto Sungai Sarik. The results of interviews and the distribution questionnaires found that teachers have not carried out practical activities in the teaching and learning process, teachers only use the literature study method as a substitute for practical activities. So that students cannot clearly describe what is obtained from the material being taught. So it can be concluded from this research that there is a need for a guided inquiry based practicum worksheet with the help of crossword puzzles on vertebrate material as a guide book for practicum activities and new innovations from previous teaching materials.